(untitled) (Research, Society and Development, 2022)
This study aims to evaluate the use and knowledge about emergency contraceptives by academics at a college in Castanhal-PA. This is a quantitative study with a cross-sectional descriptive study, being carried out in October 2020 and developed through a questionnaire containing 26 multiple-choice closed questions. Among the 205 questionnaires answered, 58.5% were health sciences academics, attending the last semesters, and there was a predominance in the age group from 18 to 23 years old, with 56.4% getting to know the drug through the internet and friends, this shows that, even being in the health area, the participants are unaware of the risks that the emergency contraceptive can cause in their body, leading to the possibility of adverse reactions. In this sense, it is essential to create health strategies for guidance by health professionals to women who are often unaware of the risks of abusive use and the appropriate place to purchase this class of medication.